The Blessing of Israel and “the Curse of the Law” : A Study of Galatians 3:10-14 - Smiles, Vincent M (Studies in Christian-Jewish Relations, 2011)
By the time he wrote Galatians, Paul was convinced that conservative Jewish-Christians were not the primary problem in the difficult debate they occasioned by their opposition to his gospel; the main problem was the Law itself and its power to require obedience to its own prescriptions. In Galatians, therefore, he turned his attack on the Law, portraying it as a “curse” on both Jews and Gentiles, the obedient and the disobedient. Paul’s critique of the Law has convinced some that Paul rejected the Jewish covenant, but the letters do not sustain that view. Paul separated the Law from the covenant, and though he abrogated the former, he never abandoned the ongoing value of the latter for both Gentiles and Jews.